ANALISIS KELAYAKAN FASILITAS UNIT PERTOLONGAN KECELAKAAN PENERBANGAN DAN PEMADAM KEBAKARAN(PKP-PK) DI BANDAR UDARA DEWANDARU KARIMUNJAWA - Kharisma Sevi Nur Safitri; Rahimudin (Jurnal Publikasi Manajemen Informatika, 2022)
Pertolongan Kecelakaan Penerbangan dan Pemadam Kebakaran (P KP-PK) or the Aircraft Rescue and Fire Fighting unit (ARFF) is a unit of the emergency response at airports that have a facility that is vehicle PKP-KP, PKP-PK operational equipment and its supporting materials and personnel are provided at each airport to provide aircraft rescue and fire fighting. In the implementation of maintenance, each airport must have a manual of procedure for vehicle maintenance and PKPPK operational support equipment must be updated according to the conditions as well as equipment and facilities with reference to the applicable standards. Objective of the assessment was to determine the system overview maintenance of PKP-PK facility at the airport. This research uses qualitative methods. The data sources used in this study are the main data sources (primary), as well as other supporting data sources in the form of written sources and documentation (secondary). Data analysis techniques in this study used data reduction analysis, data presentation, and drawing conclusions. The results of the Dewandaru Karimunjawa airport study regarding the feasibility are the PKP-PK unit facilities that have met the standards, including the main vehicle, namely Foam Tender and RIV Vehicle (Rapid Intervention Vehicle) and the fulfillment of the number of personnel, which is 11 people. Meanwhile, the facilities for the PKP-PK units that are not yet complete are the Watchroom and the Fitness Center. Meanwhile, maintenance activities for the PKP-PK unit facility equipment at Dewandaru Airport have currently been carried out in accordance with the applicable regulations, routinely and structured, even if there is damage to the facilities/equipment in the PKP-PK unit, it has also been carried out very well.